2011
DOI: 10.1128/mbio.00068-11
|View full text |Cite
|
Sign up to set email alerts
|

Surface Export of GAPDH/SDH, a Glycolytic Enzyme, Is Essential for Streptococcus pyogenes Virulence

Abstract: Streptococcal surface dehydrogenase (SDH) (glyceraldehyde-3-phosphate dehydrogenase [GAPDH]) is an anchorless major multifunctional surface protein in group A Streptococcus (GAS) with the ability to bind important mammalian proteins, including plasmin(ogen). Although several biological properties of SDH are suggestive of its possible role in GAS virulence, its direct role in GAS pathogenesis has not been ascertained because it is essential for GAS survival. Thus, it has remained enigmatic as to “how and why” S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 56 publications
(105 reference statements)
4
61
0
Order By: Relevance
“…Arguing against this is the absence of signal peptides from all of these proteins, apart from EndoS, implying cytoplasmic location (Sheldon et al, 2006;Suits et al, 2010). Conversely, there are also recent data showing that other S. pyogenes proteins with no discernible secretion sequence are indeed known to exist in an extracellular location (Jin et al, 2011;Pancholi & Fischetti, 1998), so one must acknowledge the possibility of a previously uncharacterized protein-export system in S. pyogenes (Pancholi & Fischetti, 1998). Whilst an uncharacterized protein-export machinery may play a role, there is however little direct evidence to support such a role for these enzymes in N-glycan degradation.…”
Section: Discussionmentioning
confidence: 94%
“…Arguing against this is the absence of signal peptides from all of these proteins, apart from EndoS, implying cytoplasmic location (Sheldon et al, 2006;Suits et al, 2010). Conversely, there are also recent data showing that other S. pyogenes proteins with no discernible secretion sequence are indeed known to exist in an extracellular location (Jin et al, 2011;Pancholi & Fischetti, 1998), so one must acknowledge the possibility of a previously uncharacterized protein-export system in S. pyogenes (Pancholi & Fischetti, 1998). Whilst an uncharacterized protein-export machinery may play a role, there is however little direct evidence to support such a role for these enzymes in N-glycan degradation.…”
Section: Discussionmentioning
confidence: 94%
“…Total fatty acid content and the composition of individual fatty acids in the wild-type and mutant strain of M1SF370 were custom analyzed by gas chromatography (Microbial ID) as described (24). The fatty acid profiles were analyzed with the Sherlock pattern recognition software.…”
Section: Fatty Acid Composition Analysismentioning
confidence: 99%
“…Enolase has been shown to reassociate with the cell surface (5), leaving open the possibility that a limited number of cells lyse and release their cytoplasmic contents, which then stick to the surfaces of nearby intact, unlysed cells. However, a recent study analyzing the localization of SDH in S. pyogenes showed that the protein could be held inside the cell with a hydrophobic tail, lending support to the hypothesis that there is a dedicated export pathway for this protein (16). Here we show that exogenous Ply that has been released by autolysis cannot reassociate with cells.…”
Section: Discussionmentioning
confidence: 53%
“…There are several examples of streptococcal proteins that localize to the cell wall despite lacking a signal sequence or cell wall-anchoring motif (16,22,23). Among them, enolase has been shown to reassociate with the surface of S. pneumoniae (5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation